PERTUMBUHAN DAN PRODUKSI BEBERAPA VARETAS KEDELAI TERHADAP INOKULASI BRADYRHIZOBIUM - Ayu Milani; Rosmayati Rosmayati; Luthfi A. M. Siregar (Universitas Sumatera Utara, 2013)
Growth and Production of soybean varieties of Bradyrhizobium inoculation. Demand of soybean as a protein source continues to increase, but the increasing of domestic soybean production is still low so it must import from abroad. This is due to the decline in soil fertility and agricultural land conversion to residential. The solution, soybean planting can be done by optimizing the existing land commonly called agricultural intensification. In this research, agricultural intensification is done by adding Bradyrhizobium as biofertilizer. symbiosis between soybean plants with these bacteria can directly fix the nitrogen (N) from the air and can save in the N fertilizer of inorganic form. The objective of the research was to know the responses of the soybean varieties toward Bradyrhizobium inoculation. The split plot design with three replication was used, Bradyrhizobium as main plot and soybean varieties (Anjasmoro, Burangrang, Mitani, Grobogan, Tanggamus, Detam 1, and Detam 2) as sub plot. The result showed that the Bradyrhizobium were not significant affected on all of parameters. The varieties significantly affected on plant height at 5 weeks after planted, flower initiation, the time of harvest, the seed weights per plant, and 100 seeds weight. Interaction between Bradyrhizobium inoculation and soybean varieties were not significant on all of parameters . Keyword : growth, soybean, inoculation, bradyrhizobium, variety